Chronic allergic asthma induces T-cell exhaustion and impairs virus clearance in mice - Ahn, So Yeon (2023)
Background: Allergic asthma, one of the most common types of asthma, is thought to be highly susceptible to respiratory viral infections; however, its pathological mechanism needs to be elucidated. Recent studies have found impaired T-cell function in asthmatic mice. Therefore, we aimed to investigate the way by which asthma induction affects T-cell exhaustion in the lungs and assess the relationship between T-cell exhaustion and influenza viral infection. Methods: Chronic allergic asthma mice were induced by intranasal injection of ovalbumin for 6 weeks and asthmatic features and T cell populations in lung or airway were assessed. To determine the influenza virus susceptibility, control and asthma mice were challenged with the human influenza virus strain A/Puerto Rico/8/1934 H1N1 and evaluated the survival rate, lung damage, and virus titer. Results: Six weeks of OVA sensitization and challenge successfully induced chronic allergic asthma in a mouse model showing significant increase of sera IgE level and broncho-pathological features. A significant decrease in interferon-γ-producing T-cell populations and an increase in exhausted T-cell populations in the lungs of OVA-induced asthmatic mice were observed. Asthmatic mice were more susceptible to influenza virus infection than control mice showing lower survival rate and higher virus titer in lung, and a positive correlation existed between T-cell exhaustion in the lung and virus titer. Conclusions: Asthma induction in mice results in the exhaustion of T-cell immunity, which may contribute to the defective capacity of viral protection. This study demonstrates a correlation between asthma conditions and viral susceptibility by investigating the functional characteristics of T-cells in asthma. Our results provide insights into the development of strategies to overcome the dangers of respiratory viral disease in patients with asthma.